3D–printed biphasic calcium phosphate scaffolds coated with an oxygen generating system for enhancing engineered tissue survival - Touri, Maria; Moztarzadeh, Fathollah; Abu Osman, Noor Azuan; Dehghan, Mohammad Mehdi; Mozafari, Masoud (Elsevier, 2018)
Tissue engineering scaffolds with oxygen generating elements have shown to be able to increase the level of oxygen and cell survivability in specific conditions. In this study, biphasic calcium phosphate (BCP) scaffolds with the composition of 60% hydroxyapatite (HA) and 40% beta-tricalcium phosphate (β-TCP), which have shown a great potential for bone tissue engineering applications, were fabricated by a direct-write assembly (robocasting) technique. Then, the three-dimensional (3D)-printed scaffolds were coated with different ratios of an oxygen releasing agent, calcium peroxide (CPO), which encapsulated within a polycaprolactone (PCL) matrix through dip-coating, and used for in situ production of oxygen in the implanted sites. The structure, composition and morphology of the prepared scaffolds were characterized by different techniques. The oxygen release kinetics and biological investigations of the scaffolds were also studied in vitro. The results showed that oxygen release behaviour was sustained and dependant on the concentration of CPO encapsulated in the PCL coating matrix. It was also demonstrated that the coated scaffolds, having 3% CPO in the coating system, could provide a great potential for promoting bone ingrowth with improving osteoblast cells viability and proliferation under hypoxic conditions. The findings indicated that the prepared scaffolds could play a significant role in engineering of large bone tissue implants with limitations in oxygen diffusion.